1992
DOI: 10.1136/adc.67.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Beta glucuronidase and hyperbilirubinaemia in breast fed infants of diabetic mothers.

Abstract: A prospective study was performed comparing bilirubin concentrations in 10 breast fed term infants of diabetic mothers (IDM) to those of 10 breast fed normal term infants. The ,-glucuronidase concentrations in serum and breast milk were assayed in the respective mothers. Significantly higher bilirubin concentrations were noted in the IDM group. figure).In both diabetic and non-diabetic mothers, breast milk j6-glucuronidase concentration was significantly higher (640 (205) and 216 (70) Sigma/units, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 18 publications
1
6
1
Order By: Relevance
“…In 1986 some authors suggested that ß-glucuronidase was an important factor in the pathogenesis of jaundice in breast-fed babies [4]. But these results were not confirmed by other studies [5,6].…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…In 1986 some authors suggested that ß-glucuronidase was an important factor in the pathogenesis of jaundice in breast-fed babies [4]. But these results were not confirmed by other studies [5,6].…”
contrasting
confidence: 51%
“…They showed that serum bilirubin levels were related to concentrations of ß-glucuronidase in breast milk [4]. Sirota et al [5] found higher concentrations of ß-glucuronidase in the breast milk of diabetic mothers in comparison to nondiabetic ones. However, Ince et al [6] and, recently, Erdem et al [7] did not confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies, including the recent study by La Torre et al showing statistically similar b-glucuronidase activity in breast milk fed to jaundiced vs nonjaundiced infants, have also failed to con rm this hypothesis in the general population (39). However, Sirota et al showed that signi cantly elevated bglucuronidase activity was found in the breast milk of diabetic mothers and, further, that infants of diabetic mothers had signi cantly higher serum bilirubin levels (40). This nding, in the setting of normocythemic infants of diabetic mothers, should be further investigated as a possible explanation for present and previous (9,10,41) results showing signi cantly higher serum bilirubin levels in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of pregnancy and lactation on lipoprotein and cholesterol metabolism was studied in the rat model by Smith et al 255 It is well established that cholesterol levels are elevated in normal women during pregnancy and lactation. These new findings further defined the process.…”
Section: Hyperlipoproteinemiamentioning
confidence: 99%